A deeper dive into the reminiscence bump: further evidence for the life script hypothesis. Issue 10 (26th November 2021) - Özdemir, Çağlayan; Leichtman, Michelle D.; Kreinces, Lauren J.; Pillemer, David B.
ABSTRACT: When older adults are asked to recall personal events that occurred at any point in their lives, memories from late adolescence and early adulthood are overrepresented, forming a reminiscence bump . Thematic analyses have indicated that the bump memories that emerge in response to such prompts frequently represent milestone events that are consistent with cultural life scripts. This study employed a novel method that explicitly targeted only memories of events occurring during late adolescence and early adulthood, allowing in-depth exploration of the contents and potential organising principles associated with these memories. Older adults ( N  = 197) completed an on-line survey in which they described 7 memories of personal events that had occurred at any time between the ages of 19 and 34. Content analyses indicated that memories frequently portrayed landmark events, consistent with cultural life script theory. After completing the memory task, participants who had been married or had their first child between ages 19 and 34 provided their age at the time of these events. Temporal distributions of memory ages centred on participants' ages at the time of their first marriage or childbirth also were consistent with the life script explanation for the reminiscence bump.